2005
DOI: 10.1242/dev.01685
|View full text |Cite
|
Sign up to set email alerts
|

Positioning of the midbrain-hindbrain boundary organizer through global posteriorization of the neuroectoderm mediated by Wnt8 signaling

Abstract: The organizing center located at the midbrain-hindbrain boundary (MHB)patterns the midbrain and hindbrain primordia of the neural plate. Studies in several vertebrates showed that the interface between cells expressing Otx and Gbx transcription factors marks the location in the neural plate where the organizer forms, but it is unclear how this location is set up. Using mutant analyses and shield ablation experiments in zebrafish, we find that axial mesendoderm, as a candidate tissue, has only a minor role in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 77 publications
7
94
0
2
Order By: Relevance
“…The developing Six3-null brain progressively caudalizes Early AP patterning of the forebrain partially results from a balance between caudalizing signals and their anterior antagonists (Lumsden and Krumlauf, 1996;Kudoh et al, 2002;Wilson and Houart, 2004;Rhinn et al, 2005). Wnt signaling molecules comprise a wellcharacterized family of caudalizing factors (Niehrs, 1999;Yamaguchi, 2001;Houart et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The developing Six3-null brain progressively caudalizes Early AP patterning of the forebrain partially results from a balance between caudalizing signals and their anterior antagonists (Lumsden and Krumlauf, 1996;Kudoh et al, 2002;Wilson and Houart, 2004;Rhinn et al, 2005). Wnt signaling molecules comprise a wellcharacterized family of caudalizing factors (Niehrs, 1999;Yamaguchi, 2001;Houart et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Graded posteriorizing signals specify posterior identity to the ANE (Lumsden and Krumlauf, 1996;Rhinn et al, 2005); among others, Fgfs, retinoic acid, BMPs and Wnts have been proposed as posteriorizing signals in this process (Gamse and Silve, 2000;Wilson and Rubenstein, 2000;Yamaguchi, 2001). During vertebrate head development, the level of Wnt activity specifies posterior-to-anterior fates within the neural plate (Niehrs, 1999;Heisenberg et al, 2001;Kiecker and Niehrs, 2001), and rostral forebrain development may require suppression of caudalization signals; otherwise, caudal diencephalic identity will arise (Kudoh et al, 2002;Wilson and Houart, 2004;Stern, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The organizer situated at the junction of the midbrain and anterior hindbrain -termed midbrain-hindbrain boundary (mhb) organizer or isthmic organizer -serves as a paradigm for organizer activity in the forming nervous system (Rhinn and Brand, 2001;Wurst and Bally-Cuif, 2001;Raible and Brand, 2004). The mhb organizer forms at the interface between the expression domains of two transcription factors in the neural plate -an anterior otx and a posterior gbx domain (Rhinn et al, 2005). otx and gbx expression domains initially overlap, but subsequently sort out and form a sharp interface (HidalgoSanchez et al, 1999;Garda et al, 2001;Rhinn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the diencephalon, Wnt8b signaling promotes ventral fates (Kapsimali et al, 2004) and regulates neuronal number (RussekBlum et al, 2008). Wnt8b is expressed in the dorsal telencephalon and ventral diencephalon (caudal to the commissural plate), where it is involved in patterning of the anterior-posterior neuroectoderm and telencephalon (Kelly et al, 1995;Lekven et al, 2001;Rhinn et al, 2005;Lee et al, 2006;Danesin et al, 2009). While we have shown that wnt8b regulates the expression of slit2, the downstream signaling events remain unknown.…”
Section: Discussionmentioning
confidence: 99%